Large effects of small cues: Priming selfish economic decisions - Avichai Snir; Dudi Levy; Dian Wang; Haipeng Chen; Daniel C. Levy (Bar-Ilan University, Department of Economics, 2024)
Many experimental studies report that economics students tend to act more selfishly than students of other disciplines, a finding that received widespread public and professional attention. Two main explanations that the existing literature offers for the differences found in the behavior between economists and non-economists are: (i) the selection effect, and (ii) the indoctrination effect. We offer an alternative, novel explanation: we argue that these differences can be explained by differences in the interpretation of the context. We test this hypothesis by conducting two social dilemma experiments in the US and Israel with participants from both economics and non-economics majors. In the experiments, participants face a tradeoff between profit maximization (market norm) and workers' welfare (social norm). We use priming to manipulate the cues that the participants receive before they make their decision. We find that when participants receive cues signaling that the decision has an economic context, both economics and non-economics students tend to maximize profits. When the participants receive cues emphasizing social norms, on the other hand, both economics and non-economics students are less likely to maximize profits. We conclude that some of the differences found between the decisions of economics and non-economics students can be explained by contextual cues.
Keywords: A11; A12; A13; A20; B40; C90; C91; D01; D63; D91; P10; 330; Selection; Indoctrination; Self-Interest; Market Norms; Social Norms; Economic Man; Rational Choice; Fairness; Experimental Economics; Laboratory Experiments; Priming; Economists vs. Non-Economists